Hydrooptics for ecological monitoring of marine areas - A. S. Golosnoy (Омский научный вестник)
The article describes a method for environmental monitoring of the sea area. The main indicator of environmental changes of water masses authors is considered to be a variation of its transparency. In the currently used method for measuring the transparency of water environment based on definition of depth visibility of white standard disc, which falls into the aquatic environment from the deck of a surface ship. This method for measuring the transparency has significant drawbacks, among them — the ability to determine the transparency of the water only in the surface layer dependent on weather conditions and the low accuracy of the measurement. To eliminate these drawbacks the authors propose another method of measuring the transparency of water environment based on the use of laser technologies.